Correlation Between Sagittal and Transverse Plane Fetal Nuchal Translucency Measurement - Pananya Jomphansa; Suthasinee Metaneedol; Sinart Prommas; Buppa Smanchat; Kornkarn Bhamarapravatana; Komsun Suwannarurk (Siriraj Medical Journal, 2025)
Objective: This study aimed to evaluate and compare nuchal translucency (NT) measurement between sagittal and transverse planes for aneuploidy screening. Materials and Methods: This prospective study was conducted at the antenatal clinic, department of obstetrics and gynecology, Bhumibol Adulyadej Hospital, Royal Thai Air Force, Bangkok, Thailand between November 2023 and July 2024. Subjects were singleton pregnant women who underwent fetal chromosome anomaly screening by NT measurement of both sagittal and transverse planes by transabdominal ultrasonography between 11 and 14 weeks of gestational age (GA). Demographic and clinical data were collected and evaluated. Relationship between sagittal and transverse planes measurement was analyzed. Results: A total of 295 pregnant women were recruited. The mean age and GA of participants were 31.7 years old and 12.9 weeks, respectively. Prevalence of aneuploidy was 2.7 (8/295) percent. The mean NT measurement in the sagittal plane was significantly lower than in the transverse plane (1.5 and 1.7 mm). Transverse and sagittal plane measurement exhibited a linear correlation. The cut off point of NT by transverse and sagittal approach were 2.9 mm and 3.0 mm, respectively that giving comparable diagnostic value. Conclusion: NT measurement cut off by transverse approach at 2.9 mm had comparable to 3.0 mm of sagittal approach.